2005
DOI: 10.1007/s00122-005-2039-z
|View full text |Cite
|
Sign up to set email alerts
|

Development of PCR markers for the selection of wheat stem rust resistance genes Sr24 and Sr26 in diverse wheat germplasm

Abstract: The use of major resistance genes is the most cost-effective strategy for preventing stem rust epidemics in Australian wheat crops. The long-term success of this strategy is dependent on combining resistance genes that are effective against all predominant races of the pathogen, a task greatly assisted by the use of molecular markers linked to individual resistance genes. The wheat stem rust resistance genes Sr24 and Sr26 (derived from Agropyron elongatum) and SrR and Sr31 (derived from rye) are available in w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
133
0
11

Year Published

2007
2007
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 205 publications
(144 citation statements)
references
References 26 publications
0
133
0
11
Order By: Relevance
“…PCR was performed as described by Chen et al (1998). DNA samples from the parents and breeding lines were screened using STS marker Sr24#12, which co-segregates with the Sr24/Lr24 locus (Mago et al 2005) and is used for identification of wheat lines in breeding populations with resistance to stem rust. PCR products were resolved on 8% polyacrilamide gels stained with ethidium bromide.…”
Section: Methodsmentioning
confidence: 99%
“…PCR was performed as described by Chen et al (1998). DNA samples from the parents and breeding lines were screened using STS marker Sr24#12, which co-segregates with the Sr24/Lr24 locus (Mago et al 2005) and is used for identification of wheat lines in breeding populations with resistance to stem rust. PCR products were resolved on 8% polyacrilamide gels stained with ethidium bromide.…”
Section: Methodsmentioning
confidence: 99%
“…В настоящее время эти маркеры широко используются для скрининга сортов в США и международном центре СИММИТ (William et al, 2007;Singh et al, 2008). Диа-гностические фрагменты размером 500 и 200 п. н. для Sr24#12 и Sr24#50 соответственно (Mago et al, 2005) были выявлены у положительного контроля (линии BTSR24AG) и у линии GT 96/90, что свидетельствует о наличии у нее данного гена.…”
Section: идентификация генов Sr с использованием молекулярных маркеровunclassified
“…Two markers were evaluated for Sr26 (Mago et al, 2005;Liu et al, 2010). Marker Xsr26#43 amplified a 233bp fragment from WA-1, and an amplicon did not appear (null allele) in the other accessions tested.…”
Section: Markers For Sr26mentioning
confidence: 99%
“…Markers linked to resistance genes Sr2, Sr22,Sr26,Sr32,Sr35,Sr39, and Sr40 have been reported (Hayden et al, 2004;Khan et al, 2005;Mago et al, 2005;Babiker, 2006;Dundas et al, 2007;McNeil et al, 2008;Yu et al, 2009;Mago et al, 2009;Liu et al, 2010;Mago et al, 2010;Wu et al, 2009;Niu et al, 2011;Periyannan et al, 2011), but most of these markers were identified using a specific bi-parental mapping population, and levels of polymorphism for these markers may vary with parents.…”
Section: Introductionmentioning
confidence: 99%